The returns to school-quality-adjusted education of immigrants in Germany - Huy Le Quang; Ehsan Vallizadeh (Journal for Labour Market Research, 2022)
This paper explores the role of school quality in immigrants' home countries on their earnings in Germany, using native Germans as a benchmark. We propose an empirical analysis that highlights two important insights. First, there is a substantial gap in the returns to education between natives and immigrants in Germany, especially when we consider the quality of schooling in the source country where education was obtained. In particular, lower school quality reduces the endowment advantage that immigrants possess from their education. Second, quality-adjusted education helps us to better understand the potential driving force behind the native-immigrant wage gap. We show that this measure accounts for a substantial fraction of the unexplained part in the Oaxaca-Blinder decomposition. These findings emphasize the role of the school quality in explaining the imperfect transferability of human capital of immigrants in Germany.
Keywords: I21; I26; J31; J61; 330; Earnings; Immigration; School quality; Wage gap decomposition